Hubungan status anemia, status gizi, dan faktor stres dengan siklus menstruasi pada remaja putri di Fakultas Kesehatan Masyarakat Universitas Ahmad Dahlan - Amanda, Baiq Haura Resti; Utami, Nurul Putrie (UHAMKA PRESS, 2025)
Adolescent girls are vulnerable to various health problems, one of which is menstrual cycle disturbances, affecting 11.7% of this population. These disturbances can be physiologically caused by several factors, such as anemia, nutritional status, and stress levels. This study aimed to identify the risk factors associated with menstrual cycle irregularities, focusing on anemia, nutritional status, and stress among students at the Faculty of Public Health, Universitas Ahmad Dahlan (FKM UAD). This research employed an observational approach with a cross-sectional design. A total of 100 participants were selected using purposive sampling. The instruments and tools used included the Easy Touch GcHb device, a body fat analyzer, the DASS-42 questionnaire, and a menstrual cycle questionnaire. The data were analyzed using the Chi-square statistical test. The results showed that 23% of the subjects experienced menstrual cycle irregularities. Additionally, 22% were found to be anemic, 64% had a normal nutritional status, and 79% of the subjects were classified as experiencing stress. The Chi-square analysis revealed a statistically significant association between anemia and menstrual cycle irregularities (p=0.024; OR: 3.16). However, no significant association was found between nutritional status or stress levels and menstrual cycle irregularities (p=0.913; p=0.388, respectively). In conclusion, anemia was found to be associated with menstrual cycle irregularities among adolescent girls at FKM UAD. Meanwhile, nutritional status and stress levels were not significantly associated with menstrual cycle disturbances.